INDIAN EXCHANGE TRADED FUNDS MARKET – A SYSTEMATIC LITERATURE REVIEW (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The panorama of investment opportunities  offered by Exchange Traded Funds (ETF’s) to  investors and its momentous growth since their  inception in the country has created a need to  evaluate the existing literature on Indian ETF’s.  Hence, the study aims to systematically review  74 research articles published in peer-reviewed  journals and conferences related to Indian  ETF’s. The research articles chosen for the study  are scrutinized based on various attributes to  highlight current trends in the literature and  identify future research directions. Detailed  content analysis has revealed that most of the  research articles are empirical in nature that  have predominantly used secondary data and  the leading research theme identified is the  performance evaluation of Indian ETF’s relative  to other protruding areas.
Keywords: Exchange Traded Funds; Systematic Literature Review; Indian Exchange Traded Funds.